2005
DOI: 10.1007/s10517-006-0005-7
|View full text |Cite
|
Sign up to set email alerts
|

Verapamil Aggravates Hyperkinesia Produced by Intrastriatal Administration of Picrotoxin in Rats

Abstract: The effects of slow Ca2+ channel blocker verapamil and Ca2(+)-binding agent EDTA were studied on the model of choreic hyperkinesia induced by chronic intrastriatal microinjections GABAA receptor antagonist picrotoxin. Normal and pathological movements were recorded. The test preparations facilitated the effect of picrotoxin on spontaneous and learned behavior. They exerted a permissive effect on picrotoxin-induced hyperkinesia: increase reproducibility and duration of hyperkinesia and decrease the latency of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The characteristics of spontaneous motor activity on a certain day of microinjections were compared with the results of testing of the same group of animals before implantation and with the values in control rats on the same day. Parameters of hyperkinesia were compared between two experimental groups of animals and the results of previous experiments with microinjections of PT alone [1,4,5].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of spontaneous motor activity on a certain day of microinjections were compared with the results of testing of the same group of animals before implantation and with the values in control rats on the same day. Parameters of hyperkinesia were compared between two experimental groups of animals and the results of previous experiments with microinjections of PT alone [1,4,5].…”
Section: Methodsmentioning
confidence: 99%
“…Our previous studies [1,4,5] showed that one of the mechanisms of hyperkinesia caused in rats by microinjection of picrotoxin (PT; GABA A receptor antagonist) into the neostriatum (NS) is distortion of neuronal calcium homeostasis. These data agree with the notions on the pathogenesis of Huntington's chorea [2,8] (picrotoxin hyperkinesia is an analog of this condition).…”
mentioning
confidence: 99%